2017
DOI: 10.1021/acs.jpcc.7b00943
|View full text |Cite
|
Sign up to set email alerts
|

Probing Structural, Electronic, and Magnetic Properties of Iron-Doped Semiconductor Clusters Fe2Gen–/0 (n = 3–12) via Joint Photoelectron Spectroscopy and Density Functional Study

Abstract: We present a joint experimental and theoretical study on double iron atom doped germanium clusters, Fe2Ge n –/0 (n = 3–12). The experimental photoelectron spectra of cluster anions are reasonably reproduced by theoretical simulations. The low-lying structures of the iron-doped semiconductor clusters are obtained by using an ab initio computation-based genetic-algorithm global optimization method. We find that the smaller-sized Fe2Ge n – (n = 3–8) clusters adopt bipyramid-based geometries, while the larger on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 66 publications
1
24
1
1
Order By: Relevance
“… 34 In an examination of doubly iron-doped germanium clusters, Liang and co-workers also indicated that both neutral and cationic states of Ge n Fe 2 0/− adopt polyhedral cage-like shapes with one Fe atom located inside the cage with 9 ≤ n ≤ 12. 26 Soon after the theoretical prediction of metal-encapsulated silicon cages, 40 Kumar and Kawazoe performed a series of calculations to explore the possible germanium cages stabilized by metal doping. Analogous to M@Si n clusters, they explored M@Ge n ( n = 14–16 and M = Ti, Zr, Hf, Fe, Ru, Os) clusters with various possible cage configurations such as the Frank–Kasper (FK) polyhedron, capped decahedron, fullerene-like cage and cubic cage.…”
Section: Introductionmentioning
confidence: 99%
“… 34 In an examination of doubly iron-doped germanium clusters, Liang and co-workers also indicated that both neutral and cationic states of Ge n Fe 2 0/− adopt polyhedral cage-like shapes with one Fe atom located inside the cage with 9 ≤ n ≤ 12. 26 Soon after the theoretical prediction of metal-encapsulated silicon cages, 40 Kumar and Kawazoe performed a series of calculations to explore the possible germanium cages stabilized by metal doping. Analogous to M@Si n clusters, they explored M@Ge n ( n = 14–16 and M = Ti, Zr, Hf, Fe, Ru, Os) clusters with various possible cage configurations such as the Frank–Kasper (FK) polyhedron, capped decahedron, fullerene-like cage and cubic cage.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Several transition metal (TM) atoms such as Cu, Ni, Sc, Ti and V were showed to stabilize the host structure when they are encapsulated by germanium clusters [4][5][6]. The doping with other metal atoms like Co, Fe, Mn, Ni, Ti, Zr, He, Al and Ru were also investigated [2,3,[8][9][10][11][12][13][14][15][16][17][18][19][20]. All of these studies have provided important information on the physical and chemical properties of the TM doped germanium cagelike system together with their evolution as a function of size and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Our focus in this review will be firmly on endohedral Zintl clusters [32][33][34][35][36][37] that are primarily the domain of synthetic inorganic chemistry and, very recently, materials science, but they have also been the subject of many theoretical and gas-phase spectroscopic studies. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Generally, Zintl clusters are anionic molecules made up of atoms from p-block (semi)metals. More specifically, the title of this article narrows the focus further to endohedral clusters, in which a single atom or ion of the d-or fblock elements is encapsulated within a cluster shell comprising a much larger number of p-block (semi)metal atoms from groups 13 to 15.…”
Section: Endohedral Zintl Clusters: the Impact Of Interstitial Atomsmentioning
confidence: 99%